O Brasil e a circulação de bens culturais na atualidade - Ruben George Oliven (Universidade do Vale do Rio dos Sinos (UNISINOS), 2018)
Thirty years after the publication of A moderna tradição brasileira, by Renato Ortiz, mass culture has been consolidated in Brazil, and cultural production is fully articulated to the market. Brazil has a long tradition of circulation of people, commodities, and cultural goods, which has increased in the last decades with the process of globalization. However, modernization in Brazil stumbles on social and racial inequalities. The country has serious challenges ahead if it wants to extend full citizenship to all its inhabitants.